Factors affecting purse seine catches: an observer-based analysis - TSITSIKA, E.V.; MARAVELIAS, C.D. (Mediterranean Marine Science, 2006)
A total of 72 fi shing trips were carried out by fi shery scientists onboard a purse seiner in the Pagasitikos Gulf (Greece) in an attempt to identify factors affecting total and individual species’ catches. As trawling is completely banned in the study area, purse seining is the main fi shing method. It was found that month, water depth and fi shing area affected total and Trachurus spp. catches of the purse seine fi shery, with month and water depth alone explaining 77.8% and 6.4% respectively of the total variation of the data. Signifi cant interactions observed indicate that the fl uctuations in total catches differed by month and fi shing area as well as fi shing area and water depth. Fishing area and water depth interaction were found to affect Trachurus spp. catches signifi cantly. Results also suggested that generalized linear modelling of the purse seine catches can be used to obtain representative abundance indices by reducing the observed variability. Fishery scientists’ onboard observations alongside fi sh market recordings during the same period confi rmed that each fi sher has developed an individual decision-making fi shing process. Fisher’s trip choice behaviour was found to be modulated by several factors, such as distance of fi shing grounds from the port, market demands (both in terms of species and market prices), weather conditions, alternative fi shing strategies, previously gathered information, economic pressure and personal skills. These fi ndings are discussed in the light of the need to incorporate additional quantitative information to stock abundance estimates if improved fi sheries management scenarios are to be advanced.